Pengimbasan Hasil Pelatihan Pembelajaran Coding Dan Kecerdasan Artifisial di SMKN 11 Merangin - Gina, Rolly Gios Sholid; Alhaq, Hawari; Firmansyah, M Ridho (Vox Populi: Jurnal Umum Pengabdian Kepada Masyarakat, 2025)
This community service program was implemented through the dissemination of training outcomes on coding and artificial intelligence (AI) learning at SMKN 11 Merangin. The main objective of this program was to enhance the digital literacy competencies of teachers and students, particularly in mastering fundamental programming skills and applying basic AI concepts in the learning process. The program was conducted through a series of lectures, workshops, hands-on practice, and mentoring sessions. The results indicated that both teachers and students were able to comprehend the basic concepts of coding, develop simple programs, and identify the potential applications of artificial intelligence in daily life. It is expected that this activity will contribute to improving the quality of learning in vocational schools and foster the development of a school ecosystem that supports digital competency advancement in the era of Industry 4.0.